Untapped potential: The utility of drylands for testing eco-evolutionary relationships between hosts and parasites. (August 2020) - Warburton, Elizabeth M.
Abstract: Drylands comprise over 41% of all terrestrial surface area and are home to approximately 35.5% of the world's population; however, both free-living and parasitic fauna of these regions remain relatively understudied. Yet, the very conditions that make these regions challenging to study – extreme environmental conditions and low population density for various organisms – also make them potentially untapped natural laboratories for examining eco-evolutionary relationships between hosts and parasites. Adaptations and ecological patterns illustrated by desert parasite communities can serve as exemplars within the extremes regarding the evolution of virulence, breadth of host spectra, and lifecycle strategies. This review provides relevant examples for each of these three topics using parasites from dryland regions in order to encourage future empirical tests of hypotheses regarding parasite ecology and evolution within dryland ecosystems and stimulate wider investigation into the parasitofauna of arid regions in general. As global climate changes and anthropogenic disturbance increases, desertification is a growing problem which has been labeled as a threat to global health. Thus, deserts not only provide useful natural laboratories in which to study parasite transmission but understanding parasite transmission within these habitats becomes increasingly important as larger, likely highly resource insecure, populations are projected to live on the margins of desert regions in the future. Graphical abstract: Image 1 Highlights: Drylands comprise over 41% of Earth's surface but their parasites are understudied. Desert parasite communities are exemplars within the extremes of parasite ecology. Can test hypotheses of virulence evolution, host spectra, and lifecycle strategies. Drylands can provide increasingly important insight into parasite transmission. Larger human populations are projected to live in arid regions as climate changes.